Monetary Impact of a Banking Crisis and the Conduct of Monetary Policy - Garcia-Herrero, Alicia (IMF Working Papers; Working Paper ;, 1997)
The experiences of seven countries that have undergone banking crises show that crises have significant implications for the short-run stability of the demand for money, the money multiplier, the transmission mechanism, and the signal variables of monetary policy. Monetary and credit instability, coupled with changes in the nature of the monetary and credit aggregates, complicate monetary management. These findings may require redesigning monetary instruments in favor of faster-reacting instruments, such as open market operations, and introducing additional indicators of the monetary stance, such as asset price and exchange rate movements. More frequent reviews of monetary programs may also be necessary.